PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT TELKOM WITEL MEDAN - Handri, May; Hasan, Junaidi (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
The research aims to determine the influence of leadership and communication on employee performance at PT Telkom Witel Medan. The research method uses quantitative descriptive research. The research sample was 72 people are taken from the population using the Slovin formula. The data analysis technique is testing validity, reliability test, classical assumption test, multiple linear regression analysis. Research result concluded that Leadership has a positive and significant, temporary effect Communication has no partial influence. Simultaneous Leadership and Communication has a positive and significant effect on employee performance at PT Telkom Medan Region.